Atypical presentation of Cat Eye Syndrome in an infant with Peters anomaly and microphthalmia with cyst. (1st November 2020) - Katz, Benjamin; Enright, Jennifer; Couch, Steven; Harocopos, George; Lee, Andrew R.
ABSTRACT: Purpose: To describe a unique ocular presentation of Cat Eye Syndrome and review the ocular and systemic findings associated with the syndrome. Methods: Case report with multimodal imaging. Results: A newborn female presented with a unilateral Peters anomaly with contralateral microphthalmia with cyst. The patient's other systemic findings included a hypoplastic right heart, persistent ductus arteriosus, intrauterine growth retardation, bilateral anotia, preauricular ear pits and skin tags, micrognathia, hypoplastic female genitalia, and unilateral cranial nerve VII palsy. Chromosomal microarray testing showed tetrasomy of chromosome 22 in the q11.1-q11.21 region consistent with Cat Eye Syndrome. The patient ultimately underwent a successful optical iridectomy on one side and orbitotomy with excision of the cystic mass on the other. Conclusions: The co-occurrence of unilateral Peters anomaly with contralateral microphthalmia with cyst in Cat Eye Syndrome is rare and demonstrative of the syndrome's phenotypic variability. The medical and surgical management of these patients may require a multidisciplinary approach and must be tailored to the individual findings and overall systemic health of the patient.